Effect of Genotype on Fatty Acid and Cholesterol Contents of Hen´ s Egg - Sarica, Musa; Sekeroglu, Ahmet; Karacay, Numan (Asian Journal of Chemistry, 2010)
This study was conducted to compare egg cholesterol and fatty acid contents in eggs from Denizli and Gerze which are local Turkish breeds (lay white shell colour egg) and two white and brown layer hybrids. Egg samples were obtained from 36 weeks of age hens and randomly selected for the cholesterol and fatty acid analyses. Twenty egg of each genotype were used to evaluate the effect of genotype on egg fatty acid and cholesterol contents. Turkish local breeds have low egg weight (53.94 and 54.30 g) and high egg yolk percentages (35.94 and 34.90 %) compared to the commercial hybrids (59.00 and 63.15 g; 32.67 and 32.65 %). There were differences among the genotype groups concerning egg cholesterol contents (14.63 and 15.20 mg/g yolk for pure breeds and 16.42 and 15.44 mg/g yolk for layer hybrids). Total saturated fatty acid (SFA) concentrations (32.39 and 33.11 % for pure breeds and 31.91% and 33.46% for layer hybrids); total unsaturated fatty acid (USFA) concentrations (67.61 and 66.89 % for pure breeds and 68.09 and 66.54 % for layer hybrids); USFA:SFA ratios (2.09 and 2.02 for pure breeds and 2.13 and 1.99 for layer hybrids) were found different significantly (p < 0.05). It may be considered as an advantage that the local breeds with higher egg yolk percentages were found similar or even lower than that of the layer hybrids.